Persepsi Mahasiswa terhadap Kafe sebagai Pergeseran Fungsi Ruang Belajar - Ahmad Rayya Gemintang Nusantara; Amiruddin Saleh; Harvia Atika Zahira (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to analyze the perceptions held by students of the Digital Communication and Media Study Program at the Vocational School, IPB University, regarding cafes as alternative study spaces. The phenomenon of cafes shifting from recreational venues to academic spaces is growing alongside students' increasing need for study environments that are flexible, comfortable, and supported by digital technology. This study employs a descriptive qualitative approach, utilizing in-depth interviews and documentation. The participants consisted of six students from the Class of 61 and 62, selected purposively due to their routine use of cafes for studying. The results indicate that students' positive perceptions of cafes as study spaces are shaped by three main factors: the availability of supporting facilities such as Wi-Fi, power outlets, air conditioning, and comfortable tables; an atmosphere that fosters a more conducive psychological state, thereby reducing academic stress; and opportunities for more flexible interaction and collaboration with fellow students. The findings also reveal that students view cafes not merely as places to study, but as spaces that support a balance between academic and social needs. This study concludes that cafes have transformed into a "third place" that accommodates both study activities and social interaction for students in the digital era. The research contributes to a deeper understanding of changing patterns in student study space usage within the context of digital culture and urban life.